Comparative Genomics of Bifidobacterium animalis subsp. lactis Reveals Strain-Level Hyperdiversity, Carbohydrate Metabolism Adaptations, and CRISPR-Mediated Phage Immunity - Ozge Can; Ismail Gumustop; Ibrahim Genel; Hulya Unver; Enes Dertli; Ibrahim Cagri Kurt; Fatih Ortakci (Fermentation)
Several strains of Bifidobacterium animalis subsp. lactis are blockbusters of commercial dietary supplement cocktails, widely recognized for their probiotic properties and found in various ecological niches. The present study aimed to perform an in-depth comparative genomic analysis on 71 B. animalis subsp. lactis strains isolated from diverse sources, including human and animal feces, breast milk, fermented foods, and commercial dietary supplements, to better elucidate the strain level diversity and biotechnological potential of this species. The average genome size was found to be 1.93 ± 0.05 Mb, with a GC content of 60.45% ± 0.2, an average of 1562 ± 41.3 coding sequences (CDS), and 53.4 ± 1.6 tRNA genes. A comparative genomic analysis revealed significant genetic diversity among the strains, with a core genome analysis showing that 34.7% of the total genes were conserved, while the pan-genome remained open, indicating ongoing gene acquisition. Functional annotation through EggNOG-Mapper and CAZYme clustering highlighted diverse metabolic capabilities, particularly in carbohydrate metabolism. Nearly all (70 of 71) Bifidobacterium animalis subsp. lactis strains were found to harbor CRISPR-Cas adaptive immune systems (predominantly of the Type I-E subtype), underscoring the ubiquity of this phage defense mechanism in the species. A comparative analysis of spacer sequences revealed distinct strain-specific CRISPR profiles, with certain strains sharing identical spacers that correlate with common phylogenetic clades or similar isolation sources—an indication of exposure to the same phage populations and shared selective pressures. These findings highlight a dynamic co-evolution between B. lactis and its bacteriophages across diverse ecological niches and point to the potential of leveraging its native CRISPR-Cas systems for future biotechnological applications. Our findings enhance our understanding of the genetic and functional diversity of B. animalis subsp. lactis, providing valuable insights for its use in probiotics and functional foods.